2021
DOI: 10.3390/buildings11120631
|View full text |Cite
|
Sign up to set email alerts
|

From Audits to Projects: Evaluating New York State Policy to Encourage Home Retrofit Projects

Abstract: This research explores socio-spatial characteristics of home retrofit projects in New York State and their association with the state’s free home energy audit program. Prior work by the authors found that zip codes with more elder individuals and higher levels of education are more likely to undertake an energy audit; it was also found that higher incomes may be negatively correlated with audit decisions. Less understood is the follow-up decision after an audit to undertake a retrofit. From a policy and climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…They found that this decision is positively and significantly correlated with age but is negatively correlated with renting. Hewitt and Boucher [18] analysed the New York Statesponsored retrofit projects of residential buildings from 2011 to 2016. In general, the authors confirmed a relationship between the location of audits, completed retrofit projects and pro-modernisation and pro-efficiency behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that this decision is positively and significantly correlated with age but is negatively correlated with renting. Hewitt and Boucher [18] analysed the New York Statesponsored retrofit projects of residential buildings from 2011 to 2016. In general, the authors confirmed a relationship between the location of audits, completed retrofit projects and pro-modernisation and pro-efficiency behaviours.…”
Section: Literature Reviewmentioning
confidence: 99%